Chilblain-Like Lesions (CLL) Coinciding With the SARS-CoV-2 Pandemic in Children: A Systematic Review. Issue 3 (May 2023) - Starkey, Samantha Y.; Kashetsky, Nadia; Lam, Joseph M.; Dutz, Jan; Mukovozov, Ilya M.
Chilblain-like lesions (CLL) coinciding with Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection have been described in the literature. Available reviews of the literature suggest that CLL are associated with younger age, an equal sex ratio, negative testing for SARS-CoV-2, and mild to no extracutaneous manifestations (ECM) associated with COVID-19 infection. This systematic review aims to provide a summary of reports of CLL associated with the early SARS-CoV-2 pandemic in children to clarify the prevalence, clinical characteristics, and resolution outcomes of these skin findings. Sixty-nine studies, published between May 2020 and January 2022, met inclusion criteria and were summarized in this review, representing 1, 119 cases of CLL. Available data showed a slight male predominance (591/1002, 59%). Mean age was 13 years, ranging from 0 to 18 years. Most cases had no ECM (682/978, 70%). Overall, 70/507 (14%) of patients tested positive for COVID-19 using PCR and/or serology. In the majority the clinical course was benign with 355/415 (86%) of cases resolving, and 97/269 (36%) resolving without any treatment. This comprehensive summary of pediatric CLL suggests these lesions are rarely associated with COVID-19 symptoms or test positivity.